2010
DOI: 10.1182/blood-2009-11-253534
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow macrophages maintain hematopoietic stem cell (HSC) niches and their depletion mobilizes HSCs

Abstract: In the bone marrow, hematopoietic stem cells (HSCs) reside in specific niches near osteoblast-lineage cells at the endosteum. To investigate the regulation of these endosteal niches, we studied the mobilization of HSCs into the bloodstream in response to granulocyte colonystimulating factor (G-CSF). We report that G-CSF mobilization rapidly depletes endosteal osteoblasts, leading to suppressed endosteal bone formation and decreased expression of factors required for HSC retention and self-renewal. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
761
3
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 718 publications
(806 citation statements)
references
References 48 publications
33
761
3
9
Order By: Relevance
“…10 In the past 5 years, it has emerged that G-CSF mobilizes in part by (1) blocking proliferation and osteogenic differentiation of mesenchymal stem cells (MSC), 11 (2) inducing osteoblast apoptosis 12 and (3) blocking bone formation. 13,14 This results in a dramatic reduction in the expression of chemokines and cytokines necessary to maintain and retain HSC in their endosteal and perivascular niches such as CXCL12, kit ligand (KL) and angiopoietin-1. 11,13,14 Once these endosteal niches are shutdown, HSC mobilization is initiated and possibly further amplified by protease-dependant mechanisms 13 involving neutrophil proteases, 15 CD26, 16 activation of the complement cascade 17 --19 and the thrombolytic pathway.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 In the past 5 years, it has emerged that G-CSF mobilizes in part by (1) blocking proliferation and osteogenic differentiation of mesenchymal stem cells (MSC), 11 (2) inducing osteoblast apoptosis 12 and (3) blocking bone formation. 13,14 This results in a dramatic reduction in the expression of chemokines and cytokines necessary to maintain and retain HSC in their endosteal and perivascular niches such as CXCL12, kit ligand (KL) and angiopoietin-1. 11,13,14 Once these endosteal niches are shutdown, HSC mobilization is initiated and possibly further amplified by protease-dependant mechanisms 13 involving neutrophil proteases, 15 CD26, 16 activation of the complement cascade 17 --19 and the thrombolytic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,14 Once these endosteal niches are shutdown, HSC mobilization is initiated and possibly further amplified by protease-dependant mechanisms 13 involving neutrophil proteases, 15 CD26, 16 activation of the complement cascade 17 --19 and the thrombolytic pathway. 20 It has recently been reported that specific populations of BM macrophages are necessary to maintain the function of HSC niches in the BM and for the mobilizing effect of G-CSF 13,21,22 in particular osteoblast-supportive endosteal phagocytic macrophages called osteomacs 13,23 and CD11b þ F4/80 þ Ly-6G þ phagocytic macrophages expressing CD169, which are in close association with MSC. 13,21 Whether these two macrophage populations are distinct according to niche location or functionally overlap remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations